1973
DOI: 10.1002/j.1551-8833.1973.tb01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Incidence of Klebsiella in Chlorinated Water Supplies

Abstract: Recovery and identification of Klebsiella from chlorinated water supplies substantiate the need for improved laboratory procedures in water‐treatment plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Clark and Pagel reported that the percentage of Escherichia found in the component genera of contaminated drinking water samples was reduced compared to the untreated surface water source (Clark and Pagel, 1977). Chlorination has been reported by others to increase the percentage of Klebsiella in the component coliform genera isolated from drinking water samples (Ptak et al, 1973). …”
Section: International Letters Of Natural Sciences Vol 17 123mentioning
confidence: 93%
“…Clark and Pagel reported that the percentage of Escherichia found in the component genera of contaminated drinking water samples was reduced compared to the untreated surface water source (Clark and Pagel, 1977). Chlorination has been reported by others to increase the percentage of Klebsiella in the component coliform genera isolated from drinking water samples (Ptak et al, 1973). …”
Section: International Letters Of Natural Sciences Vol 17 123mentioning
confidence: 93%
“…It is true that some, other nonpathogenic Enterobacteriaceae also occasionally occur in stools in relatively low numbers. 1551 " 1556 However, since many of these types belong to the normal microbial association of, e.g., good quality drinking water, 1557 cereals, 1558 -1562 fruits, 1563 " 1567 vegetables, 1568 " 1576 fish, 1577 " 1S79 butter and margarine, 1580 " 1582 their value as index organisms is limited to instances where they occur in unusually high numbers, demonstrating unacceptable microbial proliferation in general. 1 41 s This facet should also never be overlooked in the monitoring of heat-processed foods and meals, to which small amounts of fresh foods, such as grated cheese, salami, or fresh vegetables have been added as last minute flavoring.…”
Section: E Colimentioning
confidence: 97%
“…The fact that Klebsiella infections are primarily hospital acquired does not mitigate potential concerns about their presence in water, including chlorinated water supplies (Ptak et al, 1973). In that sense, the same can be said about Legionella.…”
Section: William a Yankomentioning
confidence: 99%
“…Klebsiella pneumoniae, however, is found in the intestinal tract of 30% of humans and 40% of animals (Geldreich and Rice, 1987). As discussed by Ptak et al (1973), Battelle Memorial Institute prepared a report for the U.S. Environmental Protection Agency in 1972 (Anderson, 1972). Concentrations may be as high as 10 8 per gram of feces (Geldreich and Rice, 1987).…”
Section: William a Yankomentioning
confidence: 99%